(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate disease patterns at the Traditional Medicine and Pharmacy Department of Le Van Thinh Hospital in Ho Chi Minh City (2022–2023), identify common disease groups according to ICD-10 and Traditional Medicine (TM), and evaluate treatment trends. Subjects and Methods: A retrospective cross-sectional study was conducted on 10,171 medical records from November 2022 to October 2023. Data included ICD-10 diagnoses, TM syndromes, and treatment methods. Statistical analysis was performed using Excel 2016. Results: The most common diseases were musculoskeletal disorders (20.77%), sleep disorders (14.12%), and gastrointestinal diseases (6.07%). According to TM, "Bi syndrome" (48.37%) was the most prevalent syndrome. A total of 93.55% of patients used finished TM products, while non-pharmacological treatments accounted for only 2.87%. Conclusion: Musculoskeletal disorders, sleep disorders, and gastrointestinal diseases were the primary disease groups at the Traditional Medicine and Pharmacy Department.